Emerging female consumers’ use of diagnostic cues in evaluating apparel assortment of South African department stores - Jacobs, B.M. (Bertha Margaretha) (University of Pretoria, 2014)
Dissertation (MConsumer Science)--Universityof Pretoria, 2013.